2012
DOI: 10.1515/1542-6580.2930
|View full text |Cite
|
Sign up to set email alerts
|

Use of X-ray Tomography for the Experimental Verification of a Mathematical Model for the Recovery of Cu and Cd in a Flow-By Porous Electrode Reactor.

Abstract: In this work a mathematical model for a flow-by electrochemical reactor operating galvanostatically for the Cu and Cd electrodeposition and hydrogen evolution reaction (HER) has been proposed. X-ray computed tomography was used to measure experimental metallic distributions. Good agreement was found between the experimental measurements and model predictions for conversion, current efficiencies, electrode potential and metallic deposit distributions. Differences were observed between experimental results and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The distribution of platinum in the Pt/Ti micromesh in the axis between the planar current feeder and the membrane was determined by X-ray CT imaging of two reconstructed stacks made with samples of the electrode. (Previous studies of metal deposits at porous electrodes using conventional X-ray imaging and low-resolution CT in electrochemical flow cells can be found in the literature [38][39][40].) Figure 6a Furthermore, the advantages of finer Pt/Ti mesh electrodes over coarser ones have also been noted in H 2 -Ce RFBs [15], where they showed an extension of the mass transport limitations at a higher operational current density.…”
Section: Pt Distribution Within the Micromesh As Revealed By Ctmentioning
confidence: 86%
“…The distribution of platinum in the Pt/Ti micromesh in the axis between the planar current feeder and the membrane was determined by X-ray CT imaging of two reconstructed stacks made with samples of the electrode. (Previous studies of metal deposits at porous electrodes using conventional X-ray imaging and low-resolution CT in electrochemical flow cells can be found in the literature [38][39][40].) Figure 6a Furthermore, the advantages of finer Pt/Ti mesh electrodes over coarser ones have also been noted in H 2 -Ce RFBs [15], where they showed an extension of the mass transport limitations at a higher operational current density.…”
Section: Pt Distribution Within the Micromesh As Revealed By Ctmentioning
confidence: 86%
“…The study of RVC's volumetric surface area by µCT has not been reported, although the cell size of a tannin-based RVC specimen was recently measured by this technique [46]. (Studies of metal deposit distribution on RVC substrates using radiography [47] and low-resolution CT [48] are available.) However, scanning conditions must be first established for maximum accuracy.…”
Section: Volumetric Surface Area Of Rvcmentioning
confidence: 99%
“…32 The physical surface area of these materials and its comparison to active electrochemical surface area is particularly important in electrochemical studies. 33,34 Examples involving conventional porous electrodes by CT include the tortuosity of carbon (C) felt, 35 the surface area of reticulated vitreous carbon (RVC) 31 and the distribution of metal deposits such as Cu and cadmium (Cd) 36 or Pt. 37,38 Related examples of the analysis of inert porous materials by CT include the determination of pore diameter distribution in SiC-Al 2 O 3 foams 39 and the study of porosity and tortuosity in SiC foams.…”
Section: Introductionmentioning
confidence: 99%